Deskripsi Metode Jarimatika Pada Materi Perkalian Di Sekolah Dasar - Miftha Huljannah; Febri Rizki Susanti Kalaka; Ingka Rizkyani Akolo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In learning mathematics, calculation techniques are indispensable. However, a common issue encountered is the lack of proficiency in calculations, whether it be addition, subtraction, multiplication, or division. Jarimatika is a method of mathematical calculation using the fingers as tools to facilitate arithmetic operations, especially multiplication. This activity aims to socialize and understand the responses of students and teachers towards the use of the Jarimatika method in elementary schools. The results of the activity showed that students were very enthusiastic during the activity and found it easier to perform multiplication operations using the Jarimatika method. The teachers' response was also very positive and they appreciated this activity. From this activity, it was proven that the Jarimatika method helps elementary school students become quicker and more proficient in multiplication operations